Promoting Hotels in the Covid-19 Era: An Exploratory Review of UK Hotels’ New Challenges - Ida Ruffolo; Jean Marguerite Jimenez (Iperstoria, 2021)
The related large-scale travel restrictions ensuing the ongoing Covid-19 pandemic have had a devastating impact on the global tourism and hospitality industry. In particular, the hotel industry is proving to be the hardest hit by the pandemic due to reduced tourism and travel along with a slowdown in economic activity (Hoisington 2020). In order to attract potential guests, hotels need to focus on consumers’ changing concerns and accommodate their legitimate requests, i.e., health safety measures and cancellation policies (UNWTO 2020). In light of this, the aim of this exploratory study is to understand to what extent hoteliers are reorganizing hotel stays to satisfy consumers’ new demands while restoring travelers’ confidence and respecting the strict safety regulations. In particular, this paper explores the crucial role of language in the hospitality sector, focusing on the linguistic devices employed by hotels on their websites to promote their facilities and services, which must now respect the strict new health and hygiene regulations imposed by the pandemic. Specifically, quantitative and qualitative methods were used to analyse a corpus of luxury hotel websites in Central England in order to examine: (i) the content included on the hotels’ websites; (ii) the language employed to promote stays during the Covid era. The preliminary findings contribute to an initial understanding of luxury hotel practices and initiatives during Covid-19 within the UK context. The results show that that there is a clear effort by luxury hotels to create a positive image as strong companies ready to face the challenges of a global pandemic. Specifically, the findings illustrate how hotels are using particular expressions to provide information related to the actions that they are taking to guarantee a safe environment, while highlighting the important role that visitors must also play in ensuring safety.